Impact of facial telangiectasias and anemia on quality of life in patients with hereditary hemorrhagic telangiectasia: a cross-sectional study using FACE-Q - Nadia Sadok; Franziska Bielefeld; Carl Nikola Martin; Eva-Marie Skoda; Katharina Klinger; Felicia Toppe; Marie Carolin Schleupner; Lukas Boosfeld; Björn Kropf; Noemi Voß; Antonia Lakomek; Anna-Lena Valina; et al. (Journal of Patient-Reported Outcomes, 2026)
Abstract Background Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disorder characterized by telangiectasias and visceral arteriovenous malformations. While the clinical manifestations are well described, its psychosocial impact—particularly with regard to visible facial telangiectasias and anemia-related appearance changes—remains insufficiently studied. This study aimed to assess appearance-related quality of life in individuals with hereditary hemorrhagic telangiectasia. Methods In this cross-sectional, single-center study, adults with hereditary hemorrhagic telangiectasia were recruited at a specialized HHT center between November 2023 and May 2024. Participants completed validated patient-reported outcome measures, including the Facial Assessment and Cosmetic Enhancement (FACE-Q) questionnaire and the Patient-Reported Outcomes Measurement Information System (PROMIS-29 +2) profile. Besides that, a standardized questionnaire assessing demographic and clinical characteristics, subjective perceptions of pallor, and cosmetic disturbance was administrated. Disease severity was assessed using the Epistaxis Severity Score and the Toronto Severity Index. Analyses were performed for the overall cohort and stratified by sex to explore potential sex differences in health-related quality of life and symptom perception. Multivariate linear regression analyses were performed to identify independent predictors of FACE-Q subscale outcomes. Results A total of 116 participants with HHT were included (mean age 60 ± 14 years; 62% were female). Subjective appearance perception showed strong effects: perceiving pallor or tiredness due to low hemoglobin levels was associated with greater appearance-related psychological distress (adjusted β = −9.09, 95% CI −17.23 to −0.94), whereas perceiving facial telangiectasias as cosmetically disturbing was associated with multiple appearance-related outcomes, including lower social function (adjusted β = −9.51, 95% CI −18.04 to −0.99), greater appearance-related psychological distress (adjusted β = −9.33, 95% CI −16.51 to −2.16), and lower satisfaction with the nose (adjusted β = −17.39, 95% CI −28.94 to −5.84). In contrast, objective clinical parameters and overall disease severity assessed by the Epistaxis Severity Score and the Toronto Severity Index were not independently associated with appearance-related quality of life. Conclusions In HHT, appearance-related quality of life is driven predominantly by subjective perception and psychosocial factors.